(untitled) (LINGUISTICA, 2015)
This study deals with the type of language style used in Mario Teguh Golden Ways Talk Show. The objectives of this study are to find out the most types of language style, to describe how the most dominant language style used and to reason for the use of the most dominant language style used by Mario Teguh in Mario Teguh Golden Ways Talk Show. The study was conducted by using descriptive qualitative method. The data of this research were utterances of Mario Teguh in Mario Teguh Golden Ways Talk Show. The findings of this research are the most dominant of language used by Mario Teguh in Mario Teguh Golden Ways is consultative style (60.6%) followed by casual style (32.45%), frozen style (5.2%), formal style(1.8%) and intimate style (0%). In this talk show Mario Teguh tends to use consulative style while he was speaking with the participants to provide more explicit background information of the participant™s problems. The consultative style in all context is used to make audiences easily understand how the topic is going on in their life.